Serum CYR61 Levels are Associated with Graves’ Ophthalmopathy and Smoking in Patients with Graves’ Disease - Cerri, Perparim; Shahida, Bushra; Lantz, Mikael; Planck, Tereza (Hormone and Metabolic Research, 2022)
Smoking is a well-known risk factor for Graves’ ophthalmopathy (GO) in patients suffering from Graves’ disease (GD). Cysteine-rich angiogenic inducer 61 (CYR61), which has multiple physiological functions, has been shown to be associated with GD and GO. In this study, we aimed to investigate the association between smoking and CYR61 concentrations in GD patients with and without GO. Serum CYR61 was measured by ELISA. The association between CYR61 concentration and GO was assessed with binary logistic regression in all patients and in subgroups of smokers and nonsmokers. The Spearman correlation coefficient was used to determine the correlations between CYR61 concentration and clinical parameters. CYR61 levels were significantly higher in GD patients with GO than in patients without GO, in smokers than in nonsmokers and in individuals older than 50 years than in those younger than 50 years. The subgroup of “GO smokers” had the highest CYR61 levels [median (IQR), 119 pg/ml (129.8)], compared with “GO nonsmokers” [84.2 pg/ml (90.8), p=0.04], “no GO smokers” [88.9 pg/ml (109.8), p=0.01] and “no GO nonsmokers” [79.4 pg/ml (129.89), p=0.003]. For each unit increase in CYR61 concentration, the odds of having GO in smokers significantly and independently increased by 1% (OR=1.010; 95% CI: 1.002–1.018, p=0.012). In conclusion, our results indicate that smoking and age increase serum CYR61 levels in patients with GD and GO. The role of CYR61 as a predictor of GO in patients with GD should be evaluated in prospective studies.
Keywords: CYR61; CCN1; Graves’ disease; Graves’ ophthalmopathy; smoking; immediate early genes